Is the record power profile repeatable? A practical analysis and interpretation in professional cyclists - Muriel, X.; Hernández-Belmonte, A.; Mateo-March, M.; Valenzuela, P. L.; Zabala, M.; Barranco-Gil, D.; Lucia, A.; Pallares, J. G. (The Journal of Strength and Conditioning Research, 2023)
This study assessed the repeatability of the Record Power Profile (RPP, i.e., the highest power output that a cyclist can attain for different effort durations under field-based conditions). We registered the RPP of 12 professional cyclists (age 32 ± 5 years) for efforts lasting between 30 seconds and 60 minutes during 3 periods of a season, each of 23-day duration: preparation (including training data only), specific (training and competition data), and competition (competition data only) periods. Repeatability was assessed using the highest 2 (RPP2), 3 (RPP3), and 5 (RPP5) values of mean maximum power obtained by the cyclists for each effort duration in each of the 3 periods. Smaller standard errors of measurement (SEM) were found as the competitive period approached, especially for short-duration efforts (i.e., 30 seconds, 1 minute, and 5 minutes, where SEM ranged from 4.3 to 12.5%, 4.1-8.5%, and 2.6-7.0% in the preparation, specific, and competition periods, respectively). However, similar SEM values were found in the 3 periods for RPP2, RPP3, or RPP5. In conclusion, the RPP appears as a repeatable parameter for monitoring field-based performance within the different phases of the season in professional cyclists.